Analisis Profitabilitas dalam Mengoptimalkan Laba pada PT Uni-Charm Indonesia TBK Tahun 2019 – 2023 - Shalsabila, Shalsabila; Firayanti, Yuni; Rosadi, Rosadi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
This research aims to evaluate the profitability ratios as an effort to optimize PT Uni- Charm Indonesia Tbk's profits. Quantitative methods are used in this research, which focus on measuring and analyzing numerical data. The data analyzed is secondary data from financial reports published on the official website of the Indonesia Stock Exchange and the official Uni- Charm website. The research results show that the profitability ratio from 2019-2023 period, which includes the return on assets ratio with an average of 4.78%, return on equity with an average of 7.94%, gross profit margin with an average of 20.82% , operating profit margin of 4.18%, and net profit margin of 4.18%, affected by a decrease in revenue, poor operational performance, unproductive assets, a decrease in net profit, a mismatch between equity and profit, a decrease in selling prices, and external disturbances . To optimize profits, PT Uni- Charm Indonesia Tbk needs to increase revenue and manage costs effectively, so that it can increase the company profitability.